Analytical Performance of Clay Paste Electrode and Graphene Paste Electrode-Comparative Study - Skowron, Ewelina; Spilarewicz-Stanek, Kaja; Guziejewski, Dariusz; Koszelska, Kamila; Metelka, Radovan; Smarzewska, Sylwia (Molecules, 2022)
The analytical performance of the clay paste electrode and graphene paste electrode was compared using square wave voltammetry (SWV) and cyclic voltammetry (CV). The comparison was made on the basis of a paracetamol (PA) determination on both working electrodes. The influence of pH and SWV parameters was investigated. The linear concentration ranges were found to be 6.0 × 10-7-3.0 × 10-5 and 2.0 × 10-6-8.0 × 10-5 mol L-1 for clay paste electrode (ClPE) and graphene paste electrode (GrPE), respectively. The detection and quantification limits were calculated as 1.4 × 10-7 and 4.7 ×10-7 mol L-1 for ClPE and 3.7 × 10-7 and 1.2 × 10-6 mol L-1 for GrPE, respectively. Developed methods were successfully applied to pharmaceutical formulations analyses. Scanning electron microscopy and energy-dispersive X-ray spectroscopy were used to characterize ClPE and GrPE surfaces. Clay composition was examined with wavelength dispersive X-ray (WDXRF).
Keywords: grafit; Carbon; Acetaminophen; paracetamol; elektrochemické techniky; Electrochemical Techniques; Clay; Graphite; Electrodes; uhlík; elektrody; jíl